Causes of long wait time in health consultation services and strategies to reduce them: an observational study in rural Haiti - Jude Altema, MD; Kenide Bien-Aime, RN; Marie Carine Roger, RN; Wendell Blaise, MD (Elsevier, 2020)
Background: WHO data show that wait times for clinic patients globally vary between 30 min and 2 h, but at Saint Boniface Hospital in Fond-des-Blancs, Haiti, wait times range between 3 h and 8 h. Wait times are important to health-care delivery since patients lose days of work and urgent cases can be delayed. In this study we aimed to analyse wait times during general and specialised medical consultations in order to identify the causes of prolonged waiting times in outpatient clinic as well as potential avenues to reduce future wait times. Methods: We administered a semi-structured questionnaire to patients in the outpatient clinic recording arrival time, time spent waiting at various check points (eg pharmacy, laboratory), and overall satisfaction with their visit. Patients were welcomed by a research worker at the hospital entrance and then observed until their release from the hospital, noting points of congestion and time spent at each service. The team then implemented three Plan-Do-Study-Act (PDSA) style process improvement interventions that aimed to decrease average wait time for patients and streamline patient flow through hospital outpatient services. We repeated the questionnaire 3 months after implementation of process improvements, capturing changes in baseline measures and outcomes. Findings: Between January and March, 2014, a total sample of 300 patients completed the questionnaire; 100 patients at baseline and 200 at follow-up. Mean total wait time was 4 h (SD 4). The main contributors to wait time were waiting for laboratory results, lack of knowledge of hospital flow, and lack of staff engagement to resolve barriers. Three PDSA cycles were done on each of these three contributors. After the PDSA cycles, the mean wait time was reduced by 1 h to 3 h (SD 2). Interpretation: Improving the clinic process with the use of PDSA cycles resulted in reduced wait times at Saint Boniface hospital. While numerous challenges remain, this study highlighted the importance of implementation of a structured triage system for outpatient clinic visits. As we progressed toward this goal, we later observed a considerable increase in the number of visits per year, which we attribute to improved patient satisfaction. Funding: None